Visible-light-driven photocatalytic degradation of toxic insecticide thiamethoxam using Ni-doped PbS nanoparticles under visible light irradiation - Farooq, Rehana; Singh, Manjeet; Singh, Jasminder; Mehta, Akansha (Frontiers in Materials, 2025)
The widespread use of the toxic insecticide Thiamethoxam (TMX) poses significant risks to environmental and human health, necessitating effective remediation methods. This study reports the successful synthesis of novel Nickel-doped Lead Sulfide (Ni-PbS) nanoparticles via a straightforward co-precipitation approach for the visible-light-driven photocatalytic degradation of TMX. Structural analysis confirmed that the Ni-PbS nanoparticles crystallize in a face-centred cubic structure. Morphological examination revealed a flower-like architecture composed of nanosheets. Optical studies showed a narrowed band gap of 2.2 eV, confirming visible-light responsiveness. X-ray photoelectron spectroscopy (XPS) further verified the presence of Pb2+, S2-, and the successful incorporation of Ni2+ into the PbS lattice. The Ni-PbS catalyst demonstrated significantly enhanced photocatalytic activity, achieving 78.93% TMX degradation within 210 min with a rate constant of 0.02225 min−1. Optimal performance was observed at pH 3 and a catalyst loading of 0.5 g/L. The catalyst also exhibited excellent stability and reusability over five consecutive cycles. Scavenger studies revealed that valence band holes (h+) and hydroxyl radicals (•OH) were the dominant reactive species driving the degradation. Overall, this work highlights Ni-PbS as a robust and efficient photocatalyst for the remediation of water contaminated with neonicotinoid insecticides.